Summarizing Analysis of Operation of American Defense Contractor Raytheon Technologies - E. O. Savchenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
The article analyzes the current situation in the American defense contractor Raytheon Technologies and assesses prospects of business development in view of present short- and long-term trends. As events in Karabachos, Syria, Libya and some other countries showed, today we can see the growing importance of war tools in pursuing foreign policy and it makes research and analysis of military-industrial complex companies more topical. Academic literature pays serious attention mainly to companies of the American military-industrial complex, which can be explained by their impact and leading positions on market. At the same time it should be pointed out that these materials demonstrate summarizing nature and do not deal with concrete and specific matters of such companies. The choice of the company Raytheon Technologies was stipulated by the fact that, due to merger with United Technologies, today it is one of the biggest American companies of the defense-industrial complex. Our analysis can support the idea of the high potential of consolidation of the defense-industrial complex sector in Western countries, which can lead to closure of unprofitable (low profitable) capacities and mass reduction of jobs, as well as degrading of technological and other related competences.